Processing of Airborne Green Leaf Volatiles for Their Glycosylation in the Exposed Plants - Sugimoto, Koichi; Iijima, Yoko; Takabayashi, Junji; Matsui, Kenji (Frontiers in Plant Science, 2021)
Green leaf volatiles (GLVs), the common constituents of herbivore-infested plant volatiles (HIPVs), play an important role in plant defense and function as chemical cues to communicate with other individuals in nature. Reportedly, in addition to endogenous GLVs, the absorbance of airborne GLVs emitted by infested neighboring plants also play a major role in plant defense. For example, the exclusive accumulation of (Z)-3-hexenyl vicianoside in the HIPV-exposed tomato plants occurs by the glycosylation of airborne (Z)-3-hexenol (Z3HOL); however, it is unclear how plants process the other absorbed GLVs. This study demonstrates that tomato plants dominantly accumulated GLV-glycosides after exposure to green leaf alcohols [Z3HOL, (E)-2-hexenol, and n-hexanol] using non-targeted LC-MS analysis. Three types of green leaf alcohols were independently glycosylated without isomerization or saturation/desaturation. Airborne green leaf aldehydes and esters were also glycosylated, probably through converting aldehydes and esters into alcohols. Further, we validated these findings in Arabidopsis mutants- (Z)-3-hexenal (Z3HAL) reductase (chr) mutant that inhibits the conversion of Z3HAL to Z3HOL and the acetyl-CoA:(Z)-3-hexen-1-ol acetyltransferase (chat) mutant that impairs the conversion of Z3HOL to (Z)-3-hexenyl acetate. Exposure of the chr and chat mutants to Z3HAL accumulated lower and higher amouts of glycosides than their corresponding wild types (Col-0 and Ler), respectively. These findings suggest that plants process the exogenous GLVs by the reductase(s) and the esterase(s), and a part of the processed GLVs contribute to glycoside accumulation. Overall, the study provides insights into the understanding of the communication of the plants within their ecosystem, which could help develop strategies to protect the crops and maintain a balanced ecosystem.